Pengaruh Fintech terhadap Kinerja UMKM pada Usaha Kuliner Kota Medan - Aurelia, Aurelia; Aurelia Vasly; Prasetio, Vasco Mario; Situmorang, Irvan Rolyesh (BUDGETING : Journal of Business, Management and Accounting, 2025)
The rapid development of digital technology has introduced financial technology (fintech) as an innovation in financial services that provides easier access for business actors, including culinary MSMEs in Medan City. This study aims to describe the influence of fintech on the performance of culinary MSMEs by emphasizing the experiences, perceptions, and practices of business owners in utilizing such services. The findings indicate that fintech contributes to improving transaction efficiency, expanding access to financing, and supporting more organized business management. However, challenges remain, such as limited digital literacy, concerns about data security, and service costs perceived as burdensome by some business actors. Therefore, fintech can be seen as both an opportunity and a challenge for culinary MSMEs in Medan, where its successful utilization depends on the readiness of entrepreneurs to integrate financial technology into their business systems.   Keywords: Culinary, Fintech, Medan, MSMEs, Performance